Konkurencyjność regionów a innowacyjność - Raszkowski, Andrzej (Regions' Competitiveness vs. Innovation, 2008)
The hereby article presents concepts related to competitiveness and innovation in regional dimension. There are covered theoretical aspects of regions' competitiveness, followed by the analysis of the level of outlays spent on innovative activities in the sector of industry, outlays on research and development (R&D), employment in research and development centres and the number of tertiary education students in the context of GDP per capita at regional level. In the summary the problems of barriers encountered in developing regional innovation potential are touched upon, as well as the role of local government in creating innovation enhancing climate. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 9-16